Application of work environment and compensation adjustments to employee performance - Munir, Ahmad Sohibul; Kurnaesih, Mia; Haryadi, Didit (Junal Ilmu Manajemen, 2024)
Employee performance is an essential factor influencing success. In an organization, this is one of the most critical functions of a company. This study aims to determine the variables that affect employee performance and develop a theoretical basis and research model. This study used an associative descriptive quantitative method with a population of 51 respondents drawn into a sample using non-probability sampling, saturated sampling / total sampling method, and data analysis techniques using linear regression with the help of SPSS software version 26. The results of this study show that the first hypothesis is that the work environment affects employee performance. Thus, the second hypothesis states that compensation does not significantly impact employee performance. The third hypothesis is that employee performance is influenced by the work environment and balance that can simultaneously improve employee performance. This research is expected to make theoretical contributions to the literature in this context, certainly in the context of human resource management.